(untitled) (Medico Legal Update, 2021)
Background: The intrauterine device (IUD) is the most popular form of reversible long-acting contraception in the world which is inserted into a woman›s uterus to prevent pregnancy. Objectives: To study knowledge among women at reproductive age about intrauterine device in baquba city. Subjects and Method: a cross-sectional study was conducting among women at reproductive age who attended outpatient clinics of Al-Batool Teaching Hospital in Baquba City from the period of the 1st of January to the 30th of June 2020. Results: Among 900 women who included in this study, with mean age about 32.2±8 years old, about 77.1% of women respondents had poor knowledge about this method of birth control. The knowledge score was affected significantly by level of education, age, residency, occupation, years of marriage, number of parity as well as the use of IUD. The main source of information is friends and relatives who represent about 93.3% and a limited role of health care providers. This may cause negative beliefs as well as many myths and rumors about IUD. Conclusion: in this study women were unaware about the basic knowledge of IUDs.